2023
DOI: 10.5194/gmd-16-535-2023
|View full text |Cite
|
Sign up to set email alerts
|

Customized deep learning for precipitation bias correction and downscaling

Abstract: Abstract. Systematic biases and coarse resolutions are major limitations of current precipitation datasets. Many deep learning (DL)-based studies have been conducted for precipitation bias correction and downscaling. However, it is still challenging for the current approaches to handle complex features of hourly precipitation, resulting in the incapability of reproducing small-scale features, such as extreme events. This study developed a customized DL model by incorporating customized loss functions, multitas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Then, we calculated the correlation patterns between the model outputs and the truth to quantify the ability of the networks to capture the spatial distribution of precipitation amounts. Additionally, the metric intersection over union (IoU) to evaluate the model's performance to classify heavy events (Prabhat et al., 2021; Wang et al., 2023) is calculated. The IoU was also quantified by considering an extreme event to be occurring for any probability higher than 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we calculated the correlation patterns between the model outputs and the truth to quantify the ability of the networks to capture the spatial distribution of precipitation amounts. Additionally, the metric intersection over union (IoU) to evaluate the model's performance to classify heavy events (Prabhat et al., 2021; Wang et al., 2023) is calculated. The IoU was also quantified by considering an extreme event to be occurring for any probability higher than 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not clearly shown that adding orography improves the fine-scale spatial variability of downscaled precipitation products from coarse to a fine grid. Recently, Wang et al (2023) developed super-resolution deep residual network models with customised loss functions to downscale the hourly precipitation data (for a downscale factor of 12) over the northern region of the Gulf of Mexico and showed their model performs better than the quantile mapping based empirical downscaling technique. In these previous studies, super-resolution deep learning models are mostly based on CNNs.…”
Section: Introductionmentioning
confidence: 99%
“…For climate projections, this will be useful for developing region-specific climate adaptation strategies. For these purposes, recent deep learning methods, especially, the super-resolution approaches, are being widely used for empirical precipitation downscaling (Vandal et al, 2017; Harilal et al, 2021; Kumar et al, 2021; Chandra et al, 2022; Wang et al, 2023). In precipitation downscaling, super-resolution models are trained to learn the relationship between the coarse-scale precipitation data and the fine-scale precipitation data, and then apply this relationship to generate high-resolution precipitation maps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide local-scale precipitation forecasting, it is common practice to downscale coarse CM forecasts to a finer grid with the use of post-processing methods. Similar to the works by Woo and Wong [2017], Vandal et al [2018], Adewoyin et al [2021], Xiang et al [2022] and Wang et al [2023], one of our main aims is to perform statistical downscaling of rainfall, that is predicting high-resolution precipitation from low-resolution weather variables. By conditioning on forecasts of future weather variables, our model can gain in reach due to the accuracy of CM weather forecasts on longer-time frames compared to statistical models directly predicting the weather.…”
Section: Introductionmentioning
confidence: 99%